Epistolario entre san Josemaría Escrivá de Balaguer y el obispo de Ávila, Santos Moro Briz, durante la Guerra Civil española (enero de 1938-marzo de 1939) / Correspondence between Saint Josemaría Escrivá and the Bishop of Avila, Santos Moro Briz, during the Spanish Civil War (January 1938- March 1939) - Constantino Anchel; Federico M. Requena (Studia et Documenta)
This paper deals with the first part of the correspondence between Saint Josemaría Escrivá and Bishop Santos Moro Briz, along the period that stretches from January 27, 1938, and June 7, 1939. There are 22 letters written by Saint Josemaría and 14 by Bishop Santos Moro. The publication of these documents is preceded by a historical introduction which shows the beginning and development of a friendship, also a general reflection on the correspondence between the two correspondents and, finally, some critical remarks on the content and meaning of the letters crossed between both of them. The documents are transcribed at the end of the paper. A chronological order has been adopted and the letters have been commented in a series of notes, some of them of a certain extension, with the purpose of making easier the understanding of the content.